Current and emerging therapies for corneal infection: a clinical and laboratory study - Ting, Darren Shu Jeng (2022)
Corneal infection or infectious keratitis (IK) is a major cause for corneal blindness worldwide. Broad-spectrum antimicrobial therapy is currently the mainstay of treatment for IK, but the efficacy is being challenged by the emergence of antimicrobial resistance. Host defense peptides (HDPs), also known as antimicrobial peptides (AMPs), are evolutionarily conserved molecules of innate immune system that are found in all kingdoms of life. HDPs have shown promise as a novel class of antimicrobial therapeutics due to their broad-spectrum and rapid antimicrobial activity against a wide array of infection with minimal risk of developing resistance. At the ocular surface, HDPs, particularly human cathelicidin (LL-37) and human beta-defensins (HBDs), have been shown to play a vital role during IK.